ON SCALING COSMOGENIC NUCLIDE PRODUCTION RATES FOR ALTITUDE AND LATITUDE USING COSMIC-RAY MEASUREMENTS - Desilets D.; Zreda M. (My University, 2001)
The wide use of cosmogenic nuclides for dating terrestrial landforms has prompted a renewed interest in characterizing the spatial distribution of terrestrial cosmic rays. Cosmic-ray measurements from neutron monitors, nuclear emulsions and cloud chambers have played an important role in developing new models for scaling cosmic-ray neutron intensities and, indirectly, cosmogenic production rates. Unfortunately, current scaling models overlook or misinterpret many of these data. In this paper, we describe factors that must be considered when using neutron measurements to determine scaling formulations for production rates of cosmogenic nuclides. Over the past 50 years, the overwhelming majority of nucleon flux measurements have been taken with neutron monitors. However, in order to use these data for scaling spallation reactions, the following factors must be considered: (1) sensitivity of instruments to muons and to background, (2) instrumental biases in energy sensitivity, (3) solar activity, and (4) the way of ordering cosmic-ray data in the geomagnetic field. Failure to account for these factors can result in discrepancies of as much as 7% in neutron attenuation lengths measured at the same location. This magnitude of deviation can result in an error on the order of 20% in cosmogenic production rates scaled from 4300 m to sea level. The shapes of latitude curves of nucleon flux also depend on these factors to a measurable extent, thereby causing additional uncertainties in cosmogenic production rates. The corrections proposed herein significantly improve our ability to transfer scaling formulations based on neutron measurements to scaling formulations applicable to spallation reactions, and, therefore, constitute an important advance in cosmogenic dating methodology.